Transformational leadership strategy as a driving force to engagement of workers: empirical study in the banking system - Latif, Wasib Bin; Md Yasin, Ida; Amin, Mohammad; Roy, Jewel Kumar; Rahaman, Md Atikur; Hossain, Md Kamal (Virtus Interpress, 2026)
This paper explores the hypothesis that transformational leadership strategy (TLS) is related to employee engagement in the branch-banking setting of a developing economy. Based on a quantitative survey of bank managers and employees (matched pairs; n = 61) and the available measures, reliability and validity have been measured, and the hypothesized TLS-engagement path has been tested through regression. Although there are recent studies and reviews that usually indicate positive links between TLS and engagement (e.g., meta-and narrative syntheses) (Bakker et al., 2023; Grah et al., 2024), our findings indicate a weak, statistically insignificant effect. The result indicates that leadership can be less motivated in banking due to contextual contingencies, including reward systems, legacy processes, or culture. We present hypotheses to apply to the job demands-resources (JD-R) theory, and in this case, leadership as a job resource might not be effective without other resources. We provide some steps that banks should take to balance leadership development with job redesign and incentives. We end with restrictions (convenience sampling, cross-sectional design) and future research (longitudinal and multi-level design and studies in other industries). Such insights provide a valuable boundary condition to other existing studies of TLS-engagement in other industries and different regions (Decuypere & Schaufeli, 2021; Bakker et al., 2023; Grah et al., 2024).